Atypical systemic leishmaniasis to be considered in the differential of patients presenting with depressed immunity. - Nuha Nuwayri-Salti; Khouzama Knio; Adham Jammoul; Rajaa Fakhoury; Karim A Sarhane; Hania Nakkash-Chmaisse (Public Library of Science (PLoS), 2012)
Systemic leishmaniasis has been known to present with prolonged fever, hepatosplenomegaly and wasting. Beside this classical form, a sub-clinical form has been identified. It is described with either one or two of the above symptoms missing; other findings have been reported instead, such as lymphadenopathy and anemia. In this report, we reveal a third unsuspected form which we are referring to as "atypical".Patients suspected to be immune-deficient were referred to our immunology specialized laboratory to study some aspects of their immune functions (not normally covered in the general laboratory). Multiple specialized tests were performed, including microscopic examinations using appropriate stains, and mainly cultures of biopsies on several types of specialized media. 19·4% of 160 patients were found to have close to normal laboratory profiles, but exhibited dysfunctional macrophages laden with Leishmania parasites.Findings such as the ones we obtained allowed us to uncover the presence of patients with an atypical form of systemic leishmaniasis. It presents with symptoms masquarading a condition in which the immune system is non functional. This predisposes patients to recurrent secondary infections resulting in clinical pictures with a great variety of signs and symptoms. These findings alerted us to the fact that systemic leishmaniasis presents with a much wider spectrum of signs and symptoms than so far suspected and is far more common than diagnosed to date. Furthermore, among these 31 patients was a number of adults. This proved that in our area systemic leishmaniasis is surely not limited to the pediatric age group. Our recommendation is to entertain the diagnosis of atypical systemic leishmaniasis in any patient with an unexplained depressed immunity state and in whom no obvious immunologic defect can be identified.